(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the evolution of digital dictionaries and their impact on language use and learning in the digital age. It defines digital dictionaries as electronic versions of traditional print dictionaries, highlighting key features such as searchability, audio pronunciations, instant updates, and cross-platform accessibility. The article discusses the advantages of digital dictionaries, including convenience, interactivity, up-to-date information, and cost-effectiveness. However, it also addresses the challenges, such as over-reliance on digital tools and inconsistencies in data quality. The article concludes by discussing the future potential of digital dictionaries, emphasizing their growing role in language learning and communication, as well as the integration of emerging technologies like AI and AR.